Risk factors for work related injury among male farmers. Issue 5 (18th December 2008) - Day, L; Voaklander, D; Sim, M; Wolfe, R; Langley, J; Dosman, J; Hagel, L; Ozanne-Smith, J
Abstract : Objective: To identify risk factors for serious farm work related injury among men. Methods: A case–control study was conducted in Victoria, Australia. Eligible cases (n = 252) were males aged ⩾16 years injured while working on a farm and scoring 2 or higher on the Abbreviated Injury Scale. Non-fatal injury cases were identified on presentation to hospital. Fatal cases (next of kin) were recruited via the Coroner's Office. Two age-matched controls per case were recruited by telephone. Data were collected with a structured telephone questionnaire. Logistic regression was used to compare risk factors between cases and controls, adjusting for design factors and average weekly hours worked. Results: The most common external causes of injury were machinery (26%), falls (19%), transport (18%), animals (17%) and being struck by an object (11%). Increased injury risk was observed for being an employee/contractor (odds ratio 1.8, 95% CI 1.2 to 2.7), not having attended farm training courses (1.5, 95% CI 1.0 to 2.1), absence of roll-over protective structures on all/almost all tractors (2.5, 95% CI 1.7 to 3.8), absence of personal protective equipment for chemical use (4.7, 95% CI 1.6 to 13.9) and a low average annual farm income of AUD5000 or less (2.7, 95% CI 1.3 to 5.6). Decreased injury risk was observed for several health related characteristics and some farm characteristics. Conclusion: We identified some risk factors possibly relevant to farm injury prevention programs. However, other factors were not associated with farm work injury suggesting these may not be as important as previously hypothesised.